2020
DOI: 10.37828/10.37828/em.2020.28.9
|View full text |Cite
|
Sign up to set email alerts
|

New data on Ovalisia (Palmar) festiva (Linnaeus) (Coleoptera: Buprestidae) and its natural enemies reported from Bulgaria

Abstract: In the last decade the cypress jewel beetle Ovalisia festiva (Linnaeus, 1767) has become a real threat in many European countries. Although it was reported from Bulgaria long ago, there is no data on its current status. The aim of this study is to present new data on cypress jewel beetle’s distribution, damage and natural enemies in the country. The research was conducted in the period 2016-2019, with 106 localities on the territory of Bulgaria examined. As a result of the current study 16 localities new for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 5 publications
0
3
0
1
Order By: Relevance
“…In Croatia this species is consider as economically important pest of T. occidentalis, particularly "Smaragd" and "Columna" cultivars (Šubić, 2018) and in Montenegro as well (Kandić, 2019). Ruseva et al (2020) report that there are data on this species in Bulgaria since about 90 years, but until the last few years it was very rare and did not pose threat to plants. At the beginning of the 21 st century, this pest was found mainly in the southwestern part of country, while the most recent surveys during 2016-2019 showed that it is widely distributed in Bulgaria and can be considered as an important pest in the landscape practice.…”
Section: Resultsmentioning
confidence: 99%
“…In Croatia this species is consider as economically important pest of T. occidentalis, particularly "Smaragd" and "Columna" cultivars (Šubić, 2018) and in Montenegro as well (Kandić, 2019). Ruseva et al (2020) report that there are data on this species in Bulgaria since about 90 years, but until the last few years it was very rare and did not pose threat to plants. At the beginning of the 21 st century, this pest was found mainly in the southwestern part of country, while the most recent surveys during 2016-2019 showed that it is widely distributed in Bulgaria and can be considered as an important pest in the landscape practice.…”
Section: Resultsmentioning
confidence: 99%
“… Metacolus unifasciatus has been previously recorded from Bulgaria as a parasitoid of Ovalisia ( Palmar ) festiva (Linnaeus, 1767) ( Coleoptera , Buprestidae ) ( Ruseva et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Klimatske promene i globalna trgovina izazvali su ogromne promene u životnoj sredini širom sveta i time pružili velike mogućnosti invazivnim i drugim vrstama da zauzmu nove teritorije, pa je to slučaj i sa tujinim krascem, Lamprodila (Palmar) festiva (Linnaeus, 1767). Tokom prethodne dekade, a verovatno i ranije, ova štetočina se brzo širila na sever i istok sa svog izvornog mediteranskog područja (Salvetti, 2013;Pedersoli, 2016;Nitzu et al, 2016;Rabl et al, 2017;Jendek et al, 2018;Bunescu & Florian, 2019;Ruseva et al, 2020).…”
Section: Uvodunclassified